2020
DOI: 10.1101/2020.10.19.20214916
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From multiplex serology to serolomics – a novel approach to the antibody response against the SARS-CoV-2 proteome

Abstract: Background: The emerging SARS-CoV-2 pandemic entails an urgent need for specific and sensitive high-throughput serological assays to assess SARS-CoV-2 epidemiology. We therefore aimed at developing a fluorescent-bead based SARS-CoV-2 multiplex serology assay for detection of antibody responses to the SARS-CoV-2 proteome. Methods: Proteins of the SARS-CoV-2 proteome and protein N of SARS-CoV-1 and common cold Coronaviruses (ccCoVs) were recombinantly expressed in E. coli or HEK293 cells. Assay performance was a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Studies by our team and others found a slightly lower specificity when including borderline results (eg, 96.3% or 98.6%). 16,26 Given the low SARS-CoV-2 prevalence in the general population, when this study was performed, test combinations with specificities greater than 99% are required to obtain valid results. A combination of 2 different tests improves accuracy markedly and has recently been used in a large seroepidemiological study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies by our team and others found a slightly lower specificity when including borderline results (eg, 96.3% or 98.6%). 16,26 Given the low SARS-CoV-2 prevalence in the general population, when this study was performed, test combinations with specificities greater than 99% are required to obtain valid results. A combination of 2 different tests improves accuracy markedly and has recently been used in a large seroepidemiological study.…”
Section: Discussionmentioning
confidence: 99%
“…15 Here, we combined ELISA with immunofluorescence as complementary tests for all samples. 16 Moreover, we further analyzed discordant samples by additional tests to maximize both specificity and sensitivity. As shown in Table 2, both initial assays independently yielded 40% to 50% of false-positive results, but these could be eliminated by a combination of the 2 readouts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunoglobulin (Ig) G (IgG) antibody levels against the S1 protein of SARS-CoV-2 were determined using an enzyme-linked immunosorbent assay (ELISA) kit (EI 2606–9601 G; Euroimmun AG) run on an Analyzer I instrument (Euroimmun AG). Multiplex SARS-CoV-2 serology was performed as recently described, and briefly, N and S1-RBD antibody levels measured in median fluorescence intensity (MFI) units [ 11 ]. Competition of sera with S1-ACE2 interaction was measured using the cPass surrogate SARS-CoV-2 neutralization test kit (L00847; Genscript, Piscataway, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%